Flexural Control of Basal Crevasse Opening Under Ice Shelves. Issue 8 (17th April 2021) - Buck, W. Roger; Lai, Ching‐Yao
Abstract: Classical analyses of basal crevasse opening do not account for the free surface of a floating ice layer. We describe a high‐resolution numerical treatment of the opening of a single crevasse in a finite thickness elastic layer floating on an inviscid substrate. For low extensional stress (less than about half of the expected maximum for a freely floating shelf) the resulting crevasse height and width match previous studies. For larger magnitude applied extensional stresses, the new results predict basal crevasse widths an order of magnitude greater than the classical solution. An analysis using the thin‐layer approximation shows that the greatly increased predicted width of basal crevasse opening results from layer bending. Given that the height and width of basal crevasses are non‐linear functions of the stress experienced by an ice shelf, the new model results may enable better estimation of buttressing stresses for different parts of ice shelves. Plain Language Summary: Basal crevasses are water filled cracks the cut through much of the ice shelves and so contribute to their breakup. A new analysis shows that basal crevasses can break through significantly more of a floating ice layer than previous models that could not consider the bending of the ice layer. This more consistent approach suggests that basal crevasses can be an order of magnitude wider than estimated by the earlier studies. A simple analytic description of flexure of ice layers correctly predicts the maximum width of basal crevasses. Key Points: The first numerical analysis of basal crevasse opening including ice shelf bending is presented Basal crevasses can be an order of magnitude wider than predicted by classical studies An analytic thin elastic plate description matches the numerical results in terms of crevasse width for a freely floating ice layer